Two additional glutaredoxins exist in Escherichia coli: glutaredoxin 3 is a hydrogen donor for ribonucleotide reductase in a thioredoxin/glutaredoxin 1 double mutant. - Aslund, F (1994)
Thioredoxin (Trx) and glutaredoxin (Grx1) are hydrogen donors for ribonucleotide reductase, the key enzyme for deoxyribonucleotide biosynthesis. The viability of a double mutant lacking both Trx and Grx1 implies the presence of a third, unknown hydrogen donor. This paper reports the purification and characterization of two proteins with glutaredoxin activity (using hydroxyethyl disulfide as a substrate) from an Escherichia coli mutant lacking Trx and Grx1 (delta trxA, grx::kan). Affinity chromatography was used to bind glutaredoxin on a glutathione-containing thiol-Sepharose column. The molecular weight of Grx2, 27,000, was atypical for glutaredoxins, whereas Grx3 had a molecular weight of 10,000. Amino acid sequence analysis revealed novel structures with putative active sites typical of glutaredoxins: Cys-Pro-Tyr-Cys. The proteins are therefore referred to as Grx2 and Grx3. The low hydrogen donor activity for ribonucleotide reductase in the crude extract was recovered in the purification of Grx3, whereas Grx2 was inactive. As a hydrogen donor for E. coli ribonucleotide reductase, Grx3 showed approximately the same Km value (0.35 microM) as Grx1, whereas its Vmax value was only 5% that of Grx1. The combination of the Grx3 hydrogen donor activity and a 25-fold induction of ribonucleotide reductase activity in a delta trxA, grx double mutant provides an explanation for its viability and deoxyribonucleotide biosynthesis. The physiological functions of Grx2 and Grx3 remain to be determined.